INCREASING ENGLISH SPEAKING SKILL THROUGH DISCUSSION (DEBATE) BY THE PROBLEM BASED INSTRUCTION (PBI) MODEL IN CLASS XII MIPA-1 MAN 2 WONOSOBO 2018/2019 ACADEMIC YEAR - Arif Yun'am (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2022)
This research is motivated by the difficulties of class XII –IPA.1 students at Madrasah Aliyah Negeri (MAN) 2 Wonosobo, Central Java, in the odd semester of the 2018/2019 academic year, to convey and ask for opinions using spoken English properly and correctly. The problem of this research is focused on the contextual learning approach with the Problem Based Instruction (PBI) model to improve English speaking skill and is a classroom action research that aims to find out the increasing in speaking skill and changes in the behavior of class XII-IPA.1 MAN 2 Wonosobo Academic Year 2018 /2019. The instruments used were tests and non-tests with observation sheets for assessing attitudes or behavior. The data obtained was then processed in a quantitative descriptive and qualitative descriptive manner. The results showed that there was an increase in students' speaking skill and changes in students' behavior for a better and enthusiastic participation in learning. The mean value obtained by students in cycle I was 73.4%. At the end of the cycle II test, the mean value increased by 7.8% to 81.2%.